Formulasi dan Evaluasi Stabilitas Fisik Sediaan Lip Balm Minyak Bekatul (Rice Bran Oil) - Sukrasno; Gayatri Simanullang; Nurul , Nurul Fadillah Islamiah (SEKOLAH TINGGI ILMU FARMASI YAYASAN PHARMASI SEMARANG, 2023)
Utilization of rice bran into oil through the extraction process. The content of rice bran can be used as a moisturizer in cosmetic preparation, especially lip balm. Lip balm is a cosmetic preparation with main components such as waxes, fats, and oils from natural or synthesized extracts to prevent lip dryness by increasing humidity and protecting it from adverse environmental effects. This research aims to determine the physical stability of lip balm preparations containing bran oil and the effect of bran oil concentration on the hedonic test results of lip balm preparations containing bran oil. This experimental research method focuses on the manufacture of lip balm preparations, the evaluation of lip balm preparations including organoleptic examination, homogeneity, melting point test, pH test, and spread-ability test during 28 days of storage. The results showed that all formulas of rice bran oil lip balm preparations met the requirements and the hedonic testing of rice bran oil lip balm preparations revealed that F1 (5% rice bran oil) was the panelist’s most preferred formula in terms of aroma, F2 (7.5% rice bran oil) was the most preferred formula in terms of texture, while F3 (10% rice bran oil) was the most preferred formula by panelists in terms of color.